Colloidal Mn2+ doped 2D (n =1) lead bromide perovskites: efficient energy transfer and role of anion in doping mechanism - Haris, Muhammed; Bakthavatsalam, Rangarajan; Kundu, Janardan (ChemistrySelect, 2018)
Mn²⁺ doping directly into APbCl3 type 3D nanocrystals, manifesting host to dopant energy transfer, have been heavily reported for illumination and display applications. However, these doped 3D ABX3 systems have low/modest exciton binding energy. Strongly bound excitons in the doped system can enhance the dopant‐host carrier exchange interactions leading to efficient energy transfer. Reported here is a simple and facile synthesis of colloidal Mn²⁺ doped (Butylammonium/octylammonium)2PbBr4 2D (n=1) perovskites that demonstrate enhanced energy transfer from strongly bound excitons of the host material to the Mn²⁺ dopant ions resulting in intense orange‐yellow emission due to spin forbidden internal transition (⁴T1 → ⁶A1) with the highest quantum yield (Mn²⁺) of 36%. Consistent with experimental evidences presented here, mechanism of this thermally aided doping process in these 2D systems, very likely, involves halide vacancy and its diffusion that precedes the cation exchange (doping) process. Owing to the high quantum yield, stability in ambient atmosphere, simplicity and scalability of the synthetic procedure, Mn²⁺ doped 2D perovskites could be beneficial as color converting phosphor material and can be utilized to further explore their magneto‐optoelectronic properties.

Controlled modulation of the structure and luminescence properties of zero-dimensional manganese halide hybrids through structure-directing metal-ion (Cd2+ and Zn2+) centers - Das, Deep Kumar; Bakthavatsalam, Rangarajan; Anilkumar, Vishnu; Mali, Bhupendra P.; Ahmed, Md Soif; Raavi, Sai Santosh Kumar; Pallepogu, Raghavaiah; Kundu, Janardan (Inorganic Chemistry, 2022)
Zero-dimensional (0D) metal halide hybrids with high exciton binding energy are excellent materials for lighting applications. Controlling/modulating the structure of the con-stituent metal halide units allows tunability of their photo-luminescence properties. 0D manganese halide hybrids are currently attracting research efforts in lighting applications due to their eco-friendly and strong emission. However, structural transformation-induced tunability of their photophysical propertieshas rarely been reported. Herein, we demonstrate a rationalsynthetic strategy to modulate the structure and luminescenceproperties of 0D Mn(II) halide hybrids utilizing the structure-directing d10metal ions (Cd2+/Zn2+). 0D metal halide hybrids ofCd2+/Zn2+, which act as hosts with tunable structures, accept Mn2+ions as substitutional dopants. This structural flexibility of thehost d10metal ions is realized by optimizing the metal-to-ligand ratio (Cd/AEPip). This reaction parameter allows structuraltransformation from an octahedral (AEPipCdMnBrOh) to a tetrahedral (AEPipCdMnBrTd) 0D Mn halide hybrid with tunableluminescence (orange -> green) with high photoluminescence quantum yield. Interestingly, when Zn2+is utilized, a tetrahedralAEPipZnMnBr structure forms exclusively with strong green emission. Optical and single-crystal X-ray diffraction structural analysisof the host and the doped system supports our experimental data and confirms the structure-directing role played by Cd2+/Zn2+centers. This work demonstrates a rational strategy to modulate the structure/luminescence properties of 0D Mn(II) halide hybrids, which can further be implemented for other 0D metal halide hybrids